Effects of Propofol on Cellular Bioenergetics in Human Skeletal Muscle Cells. Issue 3 (March 2018) - Krajčová, Adéla; Løvsletten, Nils Gunnar; Waldauf, Petr; Frič, Vladimír; Elkalaf, Moustafa; Urban, Tomáš; Anděl, Michal; Trnka, Jan; Thoresen, G. Hege; Duška, František
Abstract : Objectives: Propofol may adversely affect the function of mitochondria and the clinical features of propofol infusion syndrome suggest that this may be linked to propofol-related bioenergetic failure. We aimed to assess the effect of therapeutic propofol concentrations on energy metabolism in human skeletal muscle cells. Design: In vitro study on human skeletal muscle cells. Settings: University research laboratories. Subjects: Patients undergoing hip surgery and healthy volunteers. Interventions: Vastus lateralis biopsies were processed to obtain cultured myotubes, which were exposed to a range of 1–10 μg/mL propofol for 96 hours. Measurements and Main Results: Extracellular flux analysis was used to measure global mitochondrial functional indices, glycolysis, fatty acid oxidation, and the functional capacities of individual complexes of electron transfer chain. In addition, we used [1- 14 C]palmitate to measure fatty acid oxidation and spectrophotometry to assess activities of individual electron transfer chain complexes II–IV. Although cell survival and basal oxygen consumption rate were only affected by 10 μg/mL of propofol, concentrations as low as 1 μg/mL reduced spare electron transfer chain capacity. Uncoupling effects of propofol were mild, and not dependent on concentration. There was no inhibition of any respiratory complexes with low dose propofol, but we found a profound inhibition of fatty acid oxidation. Addition of extra fatty acids into the media counteracted the propofol effects on electron transfer chain, suggesting inhibition of fatty acid oxidation as the causative mechanism of reduced spare electron transfer chain capacity. Whether these metabolic in vitro changes are observable in other organs and at the whole-body level remains to be investigated. Conclusions: Concentrations of propofol seen in plasma of sedated patients in ICU cause a significant inhibition of fatty acid oxidation in human skeletal muscle cells and reduce spare capacity of electron transfer chain in mitochondria. Abstract : Supplemental Digital Content is available in the text.